Analisa Faktor-Faktor Mempengaruhi Penyimpangan Biaya Material Terhadap Kinerja Biaya Akhir Proyek Gedung di Kota Padang - Mukhlis, Mukhlis; Natalia, Monika; Lusyana, Lusyana; Satwarnirat, Satwarnirat; Yuma, Aulia Rahmi (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2019)
In the implementation of construction projects there are often irregularities in costs caused by, among others, materials, equipment, labor, subcontractors, overhead, and general conditions. Material is a major cost component in construction projects, so that poor material management can lead to project cost deviations. The occurrence of cost deviations can be seen from the difference between implementation costs and planning costs. To minimize these cost deviations, project control is carried out aimed at detecting as early as possible the factors that affect the cost deviations, especially in material costs. This study uses a questionnaire instrument involving 20 respondents consisting of contractors contracting M1 and M2 qualification buildings in Kota Padang, which are filled by site managers and logistics implementers. The analysis used is descriptive descriptive analysis with the help of the Statistical Product Solution Service (SPSS) program for Windows version 23.0.In this study, there are 6 sequences of dominant factors that influence material cost deviations on the final cost performance of the building project in Padang city. Among the sequences of these dominant factors, the first is external factors, namely changes in economic conditions and the occurrence of unexpected things in the force majeure, the second is material procurement factors, namely scarcity and difficulty in procuring materials on site, changes in company policy in purchase, and material cost deviations, the third is the logistical factor, namely the high rate of material damage during storage in the warehouse, the fourth is the supervision and control factors, namely the low evaluation and decision-making system, the fifth is the quality control factor which is wasteful use of material on site and the sixth factor planning and scheduling, namely errors in predicting field conditions, and future conditions and errors in planning the scope of work.